Prenatal diagnosis and successful intrauterine treatment of severe congenital hypothyroidism associated with fetal goiter. Issue 1 (12th November 2016) - Ferianec, Vladimír; Papcun, Peter; Grochal, František; Schenková, Katarína; Bártová, Michaela
Abstract: Congenital hypothyroidism with fetal goiter is a rare condition associated with severe, but possibly preventable, intrauterine and postnatal complications. Ultrasound examination after 20 weeks of pregnancy enables prenatal diagnosis and early treatment. Due to limited transplacental transport of thyroid hormones, direct intrauterine treatment is needed. So far, only a few reports of fetal goitrous hypothyroidism have been published and no consensus on adequate management exists. We present a case of severe fetal goitrous hypothyroidism diagnosed at 23 gestational weeks treated by sequential intra‐amniotic administration of L‐thyroxin. Treatment resulted in significant goiter reduction and normalization of amniotic hormone levels, and enabled uncomplicated vaginal delivery at term. Current knowledge regarding prenatal diagnosis and intrauterine treatment were unified and applied within this case and a recommendation for clinical practice is provided in this report.